NEURAMINIDASE INHIBITORS — NEW OPPORTUNITIES IN THE FLU TREATMENT IN RECENT YEARS, WHEN SOMEONE SAYS FLU, DOCTORS RECALL SUCH A THING, AS «THE VACCINATION AGAINST THE FLU». - M.D. Bakradze; V.K. Tatochenko; L.S. Namazova; E.I. Alexeeva; A.G. Surkov (Педиатрическая фармакология, 2007)
Despite it there are medications both for the prevention and treatment of the flu, like in case with any other disease. Thus, the new group of neua raminidase inhibitors belongs to the latter.Key words: flu, treatment, adults and children, neuraminidase inhibitors, oseltamivir.